Hydrophobically associating polyacrylamide thickener containing hyperbranched side chains, process and use

CN122940958APending Publication Date: 2026-10-20CNPC XIBU DRILLING ENG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611427650.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]现有技术中,增稠剂在实际应用过程中存在诸多技术缺陷:常规线性聚丙烯酰胺以超高分子量为增稠基础,存在明显性能矛盾,即高粘度体系在高速剪切工况下易发生分子链降解,导致粘度骤降,携砂性能失效;低粘度体系则携砂能力不足,无法满足施工要求

Benefits of technology

本发明提供一种含超支化侧链的疏水缔合聚丙烯酰胺增稠剂,采用反相乳液聚合法搭建油水双相复合聚合体系,搭配骨架单体、功能超支化单体、不饱和氟碳疏水单体、硅烷不饱和疏水单体及表面活性剂的多元配方体系,从根源上克服了常规产品在高矿化度、高温、高剪切复杂储层工况下易失粘、携砂稳定性差的固有缺陷,完成了增稠剂分子结构的多维度协同改性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

This invention provides a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains, along with its method and application, belonging to the field of oil and gas well fracturing and production enhancement technology. The thickener is prepared by reverse emulsion polymerization and comprises an aqueous phase and an oil phase with a mass ratio of 1:0.6 to 1:1. The aqueous phase includes: framework monomers, functional hyperbranched monomers, chain transfer agents, water-soluble initiators, and deionized water; the oil phase includes: anhydrous white oil, surfactants, hydrophobic monomers, dehydrating agents, and oil-soluble initiators. This thickener is suitable for fracturing operations in deep, high-temperature, high-salinity, and complex reservoirs. It achieves stable sand carrying at high sand ratios with low addition amounts, resulting in low reservoir damage and broad prospects for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oil and gas well fracturing and production enhancement technology, specifically to a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains, its method, and its application. Background Technology

[0002] Acid fracturing is a core process in oil and gas field production enhancement operations. Thickeners, as key functional additives in fracturing fluids, increase the viscosity of the fracturing fluid to effectively carry and suspend the proppant. Currently, oil and gas field development has entered the mid-to-late stage, with increasingly significant problems such as reservoir quality deterioration and enhanced heterogeneity. Furthermore, the development scope is gradually expanding to unconventional reservoirs and high-temperature, high-salinity reservoirs, which places more stringent technical requirements on the comprehensive performance of thickeners.

[0003] Existing thickeners suffer from numerous technical drawbacks in practical applications: conventional linear polyacrylamide, based on ultra-high molecular weight polymers, exhibits a significant performance contradiction: high-viscosity systems are prone to molecular chain degradation under high-speed shear conditions, leading to a sharp drop in viscosity and loss of proppant-carrying capacity; conversely, low-viscosity systems lack sufficient proppant-carrying capacity to meet operational requirements. For unconventional reservoir fracturing operations, a low-viscosity, high-proppant-carrying slickwater system is required, but conventional thickeners struggle to achieve both. In high-salt reservoir environments, the hydrophobic groups of hydrophobic associating polymers are easily shielded by salt ions, weakening the hydrophobic association and causing a significant decrease in fracturing fluid viscosity. Furthermore, existing thickeners have low upper temperature limits and poor thermal stability, easily experiencing performance degradation in high-temperature reservoirs, and most products have limited functionality, failing to meet the comprehensive performance requirements under complex operating conditions.

[0004] To address the aforementioned technical issues, existing technologies have undertaken relevant improvement studies: For the performance contradictions of conventional linear polyacrylamide, modifications have been made by adjusting its molecular weight distribution or introducing a small amount of branched monomers. However, these solutions only slightly alleviate the contradictions and cannot fundamentally solve the problem. Regarding the viscosity reduction issue of hydrophobic associative polymers in high-salt environments, improvements have been made by optimizing the type and content of hydrophobic monomers. However, under high salinity conditions, the technical defect of viscosity reduction still cannot be avoided. For high-temperature operating conditions, the temperature resistance of thickeners has been improved by introducing heat-resistant monomers, but their long-term thermal stability still does not meet the requirements for on-site construction. Furthermore, attempts have been made to achieve a balance of performance by compounding different types of thickeners and additives, but these methods suffer from technical problems such as complex system composition, unstable synergistic effects, and poor on-site construction operability.

[0005] In summary, existing improvement schemes have not yet overcome core technological bottlenecks: the linear molecular chain structure of conventional linear polyacrylamide has not undergone fundamental changes, failing to meet the technical requirements of low viscosity and high sand carrying capacity; the salt resistance of hydrophobic associating polymers is still insufficient, making them unsuitable for high-salt reservoir conditions; and the upper limit of the temperature resistance and long-term thermal stability of the thickener still need improvement. Furthermore, existing improvement schemes generally suffer from high costs, complex synthesis processes, or poor field adaptability, failing to simultaneously achieve core properties such as thickening, sand suspension, salt resistance, and temperature resistance. Therefore, there is an urgent need to develop a new type of thickener to address the aforementioned technical deficiencies of existing technologies and meet the actual needs of complex reservoir fracturing operations. Summary of the Invention

[0006] To address the problems existing in the prior art, this invention provides a hydrophobically associating polyacrylamide thickener containing hyperbranched side chains, a method for application, and related technologies. This thickener, through innovative molecular structure design, combines the synergistic effects of terminal carboxyl hyperbranched side chains, hydrophobic association, and silane crosslinking to overcome the performance bottlenecks of conventional thickeners. Furthermore, its preparation method is simple to operate, highly controllable, and can effectively inhibit the hydrolysis of unsaturated hydrophobic monomers of silane, ensuring the quality of the synthesized thickener.

[0007] To achieve the above objectives, the present invention provides the following technical solution: a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains, wherein the thickener is prepared by reverse emulsion polymerization and comprises an aqueous phase and an oil phase in a mass ratio of 1:0.6 to 1:1; The aqueous phase comprises: a framework monomer, a functional hyperbranched monomer, a chain transfer agent, a water-soluble initiator, and deionized water; the framework monomer comprises acrylamide and acrylic acid; the functional hyperbranched monomer comprises 2-acrylamido-2-methylpropanesulfonic acid and a carboxyl-terminated hyperbranched macromonomer; the water-soluble initiator comprises ammonium persulfate and sodium bisulfite; and the chain transfer agent comprises sodium formate. The oil phase includes: anhydrous white oil, surfactant, hydrophobic monomer, dehydrating agent, and oil-soluble initiator; the surfactant includes Span 80 and Tween 80, and the hydrophobic monomer includes unsaturated fluorocarbon hydrophobic monomer and silane unsaturated hydrophobic monomer.

[0008] Furthermore, based on the total mass of the aqueous phase, it includes 15%~20% framework monomers, 3%~10% functional hyperbranched monomers, 0.03%~0.15% chain transfer agents, 0.1%~0.3% water-soluble initiators, and the balance is deionized water.

[0009] Furthermore, the mass ratio of acrylamide to acrylic acid in the skeleton monomer is 1:4 to 1:5.

[0010] Furthermore, the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to the carboxyl-terminated hyperbranched macromonomer in the functional hyperbranched monomer is (14~15):(0.3~0.5).

[0011] Furthermore, the carboxyl-terminated hyperbranched macromonomer is prepared by esterification of a hydroxyl-terminated hyperbranched polyester with maleic anhydride. In the esterification reaction, the molar ratio of the hydroxyl group of the hydroxyl-terminated hyperbranched polyester to the maleic anhydride is 1:1.0 to 1:1.1, the reaction temperature is 60℃ to 65℃, the reaction time is 4h to 6h, and the acid value of the obtained carboxyl-terminated hyperbranched macromonomer is 92% to 96% of the hydroxyl value of the hydroxyl-terminated hyperbranched polyester.

[0012] Furthermore, the terminal hydroxyl hyperbranched polyester has at least one of the following structural features: (a) a branching degree of 0.4 to 0.7; (b) a backing structure of aliphatic hyperbranched polyester; (c) a backing structure of aromatic hyperbranched polyester; (d) a hydroxyl value of 490 mg KOH / g to 560 mg KOH / g; (e) a number-average molecular weight of 1000 to 10000; and (f) an average number of terminal hydroxyl groups of 8 to 48 per molecule.

[0013] Furthermore, based on the total mass of the oil phase, it includes 0.1%~1.0% unsaturated fluorocarbon hydrophobic monomers, 0.1%~0.9% silane unsaturated hydrophobic monomers, 0.01%~0.08% dehydrating agent, 8%~16% surfactant, 0.05%~0.15% oil-soluble initiator, and the balance is anhydrous white oil.

[0014] Furthermore, the mass ratio of Span 80 to Tween 80 in the surfactant is 4:1 to 6:1.

[0015] Furthermore, the unsaturated fluorocarbon hydrophobic monomer is a medium- to long-chain fluorinated acrylate; the silane unsaturated hydrophobic monomer is one or more of γ-methacryloyloxypropyltrimethoxysilane, vinyltriethoxysilane, and vinyltrimethoxysilane.

[0016] Furthermore, the hydrophobic associating polyacrylamide thickener containing hyperbranched side chains uses polyacrylamide as its molecular backbone, and the molecular backbone is grafted with terminal carboxyl hyperbranched side chains, fluorocarbon hydrophobic groups, and silane crosslinking active groups; the degree of branching of the hydrophobic associating polyacrylamide thickener containing hyperbranched side chains is 0.70~0.75, and the molecular weight is 13 million.

[0017] Furthermore, the hydrophobically associating polyacrylamide thickener containing hyperbranched side chains possesses the following performance parameters: Under high-salt conditions with a total hardness of 50,000 mg / L, the viscosity retention rate at room temperature is ≥80%, and the viscosity retention rate under high-temperature conditions below 130℃ is ≥65%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is ≥85%; the shear recovery time is ≤30s; a 0.25% aqueous solution of hydrophobic associating polyacrylamide thickener containing hyperbranched side chains, with 20 / 40 mesh ceramsite support and a sand ratio of 35%, has a static suspended sedimentation rate of ≤0.5 cm / min; the critical association concentration is 0.1%.

[0018] This invention provides a method for preparing a hydrophobically associating polyacrylamide thickener containing hyperbranched side chains, employing a reverse emulsion polymerization method, comprising the following steps: Anhydrous white oil, surfactant, unsaturated fluorocarbon hydrophobic monomer, silane unsaturated hydrophobic monomer, and dehydrating agent are mixed and stirred evenly to obtain the oil phase; Acrylamide, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid, carboxyl-terminated hyperbranched macromonomer, sodium formate, and ammonium persulfate were dissolved in deionized water, the pH of the system was adjusted to 5.5-6.5, and the mixture was stirred evenly to obtain an aqueous phase. The aqueous phase is slowly added to the oil phase at a constant rate, and continuous high-speed shear emulsification is carried out to obtain a water-in-oil pre-emulsion; Nitrogen gas was introduced into the pre-emulsion to remove oxygen. After the oxygen was removed, the temperature was raised to the target reaction temperature. An oil-soluble initiator and an aqueous solution of sodium bisulfite were added dropwise, and the mixture was kept at a constant temperature for 4-6 hours to obtain a copolymer emulsion with a dual network topology. The copolymer emulsion was vacuum dried, pulverized, and sieved to obtain a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains.

[0019] Furthermore, the stirring speed for the oil phase preparation was 300 r / min to 500 r / min, and the stirring time was 20 min to 30 min; the stirring speed for the aqueous phase preparation was 400 r / min to 600 r / min, and the stirring time was 30 min to 40 min; the droplet acceleration rate of the aqueous phase was 5 mL / min to 10 mL / min, and the high-speed shear emulsification time was 15 min to 20 min.

[0020] Furthermore, the nitrogen deoxygenation time for the pre-emulsion is 20-30 minutes, the target reaction temperature is 40-45°C, and the initiator drop rate is 2-5 mL / min. During polymerization, when the temperature rise rate exceeds 3°C / min, a cold bath is used for cooling.

[0021] Furthermore, the vacuum drying temperature is 95℃, the drying time is 5h~7h, and the powder is passed through an 80-100 mesh sieve.

[0022] This invention also provides the application of the above-mentioned hydrophobic associating polyacrylamide thickener containing hyperbranched side chains in oil and gas reservoir fracturing fluid. Using water as a solvent, the hydrophobic associating polyacrylamide thickener containing hyperbranched side chains is added at a concentration of 0.25% to prepare the fracturing fluid. The fracturing fluid prepared is suitable for fracturing operations in high-salinity oil and gas reservoirs with a temperature ≤220℃, and the maximum sand ratio reaches 38%.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects: This invention provides a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains. It employs a reverse emulsion polymerization method to construct an oil-water two-phase composite polymerization system, combined with a multi-component formulation system consisting of a backbone monomer, a functional hyperbranched monomer, an unsaturated fluorocarbon hydrophobic monomer, a silane unsaturated hydrophobic monomer, and a surfactant. This fundamentally overcomes the inherent defects of conventional products, such as easy loss of adhesion and poor sand-carrying stability, under complex reservoir conditions of high salinity, high temperature, and high shear. It achieves multi-dimensional synergistic modification of the thickener's molecular structure.

[0024] Furthermore, this invention specifies the proportions of each component in the aqueous and oil phases, the monomer blending ratio, and the preparation process and structural parameters of the hyperbranched monomers. Through formulation control and directional optimization of monomer structures, it solves the practical production problems of disordered component ratios, uneven molecular branching structures, large performance fluctuations, and inconsistent modification effects between different batches in conventional modified thickeners. In particular, by clearly defining the structure of the terminal hydroxyl hyperbranched polyester substrate and the esterification preparation parameters, the uniformity and structural integrity of the terminal carboxyl hyperbranched side links are ensured, effectively improving the elasticity and encapsulation ability of the polymer molecular network.

[0025] This invention further optimizes and limits the specific types and amounts of unsaturated fluorocarbon hydrophobic monomers and silane unsaturated hydrophobic monomers, while also optimizing the surfactant formulation. This structural design solves the technical problems of traditional ionic polyacrylamide, such as susceptibility to salt ion shielding, significant viscosity decay in high-salt environments, and low upper temperature resistance. By utilizing the strong hydrophobicity of fluorocarbon groups and the self-tackifying effect of salt, combined with the synergistic regulatory effect of surfactants on the viscoelasticity of the system, the product's salt resistance and thickening ability are significantly improved, allowing the product to be directly adapted to the construction environment of ultra-high salinity reservoirs.

[0026] Furthermore, this invention uses a polyacrylamide polymer chain formed by the copolymerization of acrylamide and acrylic acid as the molecular backbone. It further grafts terminal carboxyl hyperbranched side chains, fluorocarbon hydrophobic groups, and silane crosslinking active groups onto the molecular backbone, constructing a dual-network topology structure coupled with physical association and covalent crosslinking. Simultaneously, it precisely controls the branching degree and molecular weight parameters of the product. This solves the contradiction commonly found in traditional fracturing fluid thickeners: rapid viscosity reduction under high shear and poor proppant carrying capacity under low viscosity. Utilizing the cage effect of the hyperbranched structure, it achieves comprehensive encapsulation of the proppant. Under moderate molecular weight conditions, it simultaneously achieves low reservoir damage, high shear resistance, and excellent proppant carrying performance, exhibiting excellent shear recovery and fully meeting the actual operational needs of low viscosity and high proppant carrying capacity in oilfields.

[0027] Furthermore, this invention optimizes the preparation process of the reverse emulsion polymerization method. Through multiple protection mechanisms—water-in-oil physical isolation, weak acidity control of the aqueous phase, and chemical dehydration of the oil phase—the complete generation of the dual-network topology is effectively guaranteed. The reaction conditions are mild and controllable, the process has good repeatability, it is fully adaptable to large-scale industrial production, and it can also significantly reduce the overall cost of preparation.

[0028] Furthermore, this invention also defines the industrial application parameters for the thickener, using a low-concentration addition method to formulate a water-based fracturing fluid, directly adaptable to fracturing operations in complex high-temperature, high-salinity reservoirs. This solves the practical engineering problems of traditional fracturing fluid systems, such as large reagent consumption, high reservoir damage, poor adaptability to high-temperature, high-salinity conditions, low sand ratios, and limited production enhancement effects. It enables stable sand-carrying operations with high sand ratios, and its performance shows no significant degradation under long-term high-temperature conditions. Attached Figure Description

[0029] Figure 1 The image shows the appearance of a fracturing fluid prepared using a hydrophobically associating polyacrylamide thickener containing hyperbranched side chains obtained in Example 1.

[0030] Figure 2 The first image shows the initial static suspended sand state of 30% 20 / 40 ceramsite proppant (right), and the second image shows the suspended sand state of 30% 20 / 40 ceramsite proppant after 30 minutes (left). Detailed Implementation

[0031] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0032] This invention provides a hydrophobically associating polyacrylamide thickener containing hyperbranched side chains. Using polyacrylamide as the molecular backbone, terminal carboxyl-terminated hyperbranched side chains, fluorocarbon hydrophobic groups, and silane crosslinking active groups are grafted onto the molecular backbone. The resulting hydrophobically associating polyacrylamide thickener containing hyperbranched side chains can effectively solve the performance defects of existing thickeners in complex reservoir conditions. Its key performance indicators have been verified by actual testing as follows: (1) The degree of branching is 0.70~0.75, which can take into account both the viscoelasticity and shear stability of the thickener; (2) Under high salt conditions with a total hardness of 50000 mg / L, the viscosity retention rate is ≥80% at room temperature and ≥65% at high temperature conditions below 130℃, which can be adapted to high salt and high temperature reservoir environments. (3) Under high-speed shearing conditions of 3400 r / min, the viscosity retention rate is ≥85%, which indicates excellent shear resistance. (4) Shear recovery time ≤30s, which can quickly restore viscoelasticity and ensure sand carrying performance; (5) A 0.25% aqueous solution of hydrophobic associative polyacrylamide thickener containing hyperbranched side chains, under the conditions of 20 / 40 mesh ceramsite proppant and 35% sand ratio, has a static suspended sand settling rate ≤0.5cm / min, and excellent sand carrying performance. (6) The critical association concentration is 0.1%, and excellent thickening effect can be achieved with low addition amount, reducing the cost of on-site application.

[0033] The above-mentioned hydrophobic associative polyacrylamide thickener containing hyperbranched side chains is prepared by reverse emulsion polymerization. The raw material composition, by mass percentage, includes an aqueous phase and an oil phase, wherein the mass ratio of the aqueous phase to the oil phase, m1:m2, is 1:0.6 to 1:1. This ratio range can ensure the stability of the water-in-oil emulsion and provide a suitable reaction environment for monomer polymerization.

[0034] The specific raw material ratios are defined as follows: the aqueous phase, based on the total mass m1 of the aqueous phase, includes 15%~20% framework monomers, 3%~10% functional hyperbranched monomers, 0.03%~0.15% chain transfer agents, 0.1%~0.3% water-soluble initiators, and the balance is deionized water, with the mass percentage of deionized water being 60%~75%, which serves as the aqueous phase dispersion medium; The oil phase, based on the total mass m2 of the oil phase, includes 0.1%~1.0% unsaturated fluorocarbon hydrophobic monomers, 0.1%~0.9% silane unsaturated hydrophobic monomers, 0.01%~0.08% dehydrating agent, 8%~16% surfactant, 0.05%~0.15% oil-soluble initiator, with the balance being anhydrous white oil.

[0035] The total mass of the aforementioned skeleton monomers, functional hyperbranched monomers, unsaturated fluorocarbon hydrophobic monomers, and silane unsaturated hydrophobic monomers accounts for 20% to 30% of the total mass of the aforementioned hydrophobic associative polyacrylamide thickeners containing hyperbranched side chains.

[0036] In a further preferred embodiment, the backbone monomer is polyacrylamide obtained by blending acrylic acid and acrylamide, with a mass ratio of m(acrylic acid):m(acrylamide) = 1:4~1:5. Acrylamide is a nonionic monomer, ensuring the basic thickening properties and water solubility of the thickener; acrylic acid is an anionic monomer, improving the solubility and stability of the thickener in a salt environment. The blend achieves a preliminary balance between thickening performance and salt resistance, providing a stable molecular backbone for grafting carboxyl-terminated hyperbranched side chains, fluorocarbon hydrophobic groups, and silane crosslinking active groups. The ratio directly determines the basic thickening effect and molecular chain regularity of the thickener.

[0037] Further preferred, the functional hyperbranched monomer is a combination of 2-acrylamido-2-methylpropanesulfonic acid and a carboxyl-terminated hyperbranched macromonomer, with a mass ratio of m(2-acrylamido-2-methylpropanesulfonic acid):m(carboxyl-terminated hyperbranched macromonomer) = (14~15):(0.3~0.5). The 2-acrylamido-2-methylpropanesulfonic acid structure contains a strongly polar sulfonic acid group, exhibiting excellent temperature and salt resistance, effectively improving the stability of the thickener in high-temperature and high-salt reservoir environments and preventing the thickener molecular chain from coiling under high-salt conditions. The carboxyl-terminated hyperbranched macromonomer is used to graft carboxyl-terminated hyperbranched side chains onto the polyacrylamide molecular backbone, providing the core structural basis for the cage effect, thereby achieving high suspension performance at low molecular weight. The specific preparation method is as follows: Step 1: Select hydroxyl-terminated hyperbranched polyester as the starting material. Place the hydroxyl-terminated hyperbranched polyester in a vacuum drying oven and vacuum dry it for 4 hours at 80℃ and -0.1MPa to remove trace amounts of moisture from the raw material and avoid side reactions between moisture and subsequent reaction reagents, which could affect the preparation quality of the hydroxyl-terminated hyperbranched macromonomer.

[0038] Step 2: In a three-necked flask equipped with a mechanical stirrer, a reflux condenser, and a nitrogen inlet, add 100 parts by weight of vacuum-dried terminal hydroxyl hyperbranched polyester, followed by 300 parts by weight of anhydrous acetone as the reaction solvent. Stir until the raw materials are completely dissolved, forming a homogeneous and transparent solution. Then add the catalyst, either p-toluenesulfonic acid or triethylamine, with p-toluenesulfonic acid added at 0.5-1.0 parts by weight and triethylamine added at 0.2-0.5 parts by weight. Stir to ensure the catalyst is evenly dispersed in the reaction system, guaranteeing a uniform reaction. Under continuous nitrogen protection, maleic anhydride is slowly added dropwise at a molar ratio of hydroxyl groups in the terminal hydroxyl hyperbranched polyester to maleic anhydride of 1:1.0-1:1.1. After the addition is complete, the temperature is raised to 60℃-65℃ and the reaction is maintained at this temperature for 4-6 hours. During this period, the reaction progress is monitored in real time using thin-layer chromatography or infrared spectroscopy. When the characteristic peak of the anhydride (approximately 1780 cm⁻¹) is reached... -1When the hydroxyl group completely disappears, the reaction is considered to have reached its endpoint, ensuring that the hydroxyl group is fully converted into the carboxyl group.

[0039] Step 3: After the reaction is complete, the reaction solution is naturally cooled to room temperature, and then excess ice-cold ether is slowly poured in to precipitate the target product from the reaction system. The precipitate is collected by filtration. The precipitate is washed three times with a mixture of acetone and ether (volume ratio 1:3) to remove unreacted raw materials and byproducts. The washed precipitate is then placed in a vacuum drying oven and dried under vacuum at 40°C to constant weight to obtain a white to pale yellow solid powder, which is the terminal carboxyl hyperbranched macromonomer.

[0040] Actual measurements showed that the acid value of the prepared carboxyl-terminated hyperbranched macromonomer was 92%~96% of the hydroxyl value of the hydroxyl-terminated hyperbranched polyester (90%~95% without a catalyst), indicating that most of the hydroxyl groups had been successfully converted into carboxyl groups, and could smoothly undergo grafting reactions with the polyacrylamide molecular backbone.

[0041] It should be noted that the above-mentioned hydroxyl-terminated hyperbranched polyester can be selected from products having at least one of the following structural features, all of which can achieve the technical effects of the present invention: (a) a branching degree of 0.4 to 0.7; (b) its skeleton is an aliphatic hyperbranched polyester skeleton; (c) its skeleton is an aromatic hyperbranched polyester skeleton; (d) a hydroxyl value of 490 mg KOH / g to 560 mg KOH / g; (e) a number average molecular weight of 1000 to 10000; and (f) an average number of hydroxyl groups per molecule of 8 to 48.

[0042] Preferably, the aliphatic hyperbranched polyester skeleton and the aromatic hyperbranched polyester skeleton are heat-resistant.

[0043] Preferably, the hydroxyl-terminated hyperbranched polyester is Boltorn H20, which has a hydroxyl value of about 490 mg KOH / g to 520 mg KOH / g, a number average molecular weight of about 2100, and a branching degree ≥0.5.

[0044] Further preferred, the hydrophobic monomer is a combination of unsaturated fluorocarbon hydrophobic monomer and silane unsaturated hydrophobic monomer. The two work synergistically to achieve the core functions of salt self-thickening and temperature-resistant crosslinking, respectively, thus solving the technical defects of existing thickeners such as poor salt resistance and insufficient temperature resistance.

[0045] Among them, the unsaturated fluorocarbon hydrophobic monomer is a medium-to-long chain fluorinated acrylate, preferably one or two of dodecafluoroheptyl methacrylate (total carbon number C11) and tridecafluorooctyl methacrylate (total carbon number C12); the molecular structure of this type of monomer contains fluorocarbon groups, which have extremely strong hydrophobicity. Under high salt conditions, it can achieve salt self-viscosity enhancement effect through hydrophobic association, thereby increasing the viscosity of fracturing fluid in high salt environment; The silane unsaturated hydrophobic monomers are selected from one or more of γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, and vinyltrimethoxysilane. After polymerization, these monomers can be slowly hydrolyzed in an aqueous environment to form a stable Si-O-Si covalent cross-linked network, which effectively improves the temperature resistance and molecular structure stability of the thickener and avoids thermal degradation of the thickener in high-temperature reservoirs.

[0046] Further preferably, the surfactant is a blend of Span 80 and Tween 80 as the emulsifier, with a mass ratio of m(Span 80):m(Tween 80) = 4:1 to 6:1. Span 80 is an oil-soluble emulsifier that reduces the surface tension of the oil phase, while Tween 80 is a water-soluble emulsifier that reduces the surface tension of the aqueous phase. The blend forms a stable water-in-oil emulsion, ensuring polymerization at the interface between the aqueous and oil phases. Simultaneously, the blended surfactant synergistically interacts with the hydrophobic monomer to regulate the viscoelasticity of the thickener system, further enhancing the thickener's sand-carrying capacity.

[0047] More preferably, the water-soluble initiator is a mixture of ammonium persulfate and sodium bisulfite, with a mass ratio of m(ammonium persulfate):m(sodium bisulfite) = 2:1. This water-soluble initiator is a redox initiation system, which can initiate the polymerization reaction of skeletal monomers and functional hyperbranched monomers in the aqueous phase at a lower temperature. More preferably, the oil-soluble initiator is one or more of azobisisobutyronitrile or azobisisobutyronitrile. This oil-soluble initiator can slowly decompose in the oil phase environment, initiating interfacial polymerization between the hydrophobic monomer in the oil phase and the monomer in the aqueous phase, ensuring that the hydrophobic groups are uniformly grafted onto the molecular chain of polyacrylamide.

[0048] Further preferred, sodium formate is selected as the chain transfer agent. Its function is to regulate the molecular weight of the thickener, controlling it to around 13 million. This molecular weight range can achieve high sand-suspending performance at a low molecular weight, while avoiding the problem of excessively high fracturing fluid viscosity and reservoir damage caused by a large molecular weight, thus balancing the needs of construction safety and reservoir protection.

[0049] Further preferred, the anhydrous white oil uses one or two of the following: 5#, 10#, and 15# as the oil phase dispersion medium. Its function is to isolate the aqueous phase and the oil phase, forming a stable water-in-oil emulsion system. At the same time, it can avoid premature hydrolysis caused by direct contact between the silane unsaturated hydrophobic monomer and the aqueous phase, ensuring the effective utilization rate of the silane unsaturated hydrophobic monomer, and thus ensuring the complete formation of the Si-O-Si covalent cross-linked network in the thickener.

[0050] Further preferred, the dehydrating agent is triethyl orthoformate, which has two functions: first, it can effectively remove trace amounts of water diffused from the aqueous phase in the oil phase, improve the hydrolysis environment of silane unsaturated hydrophobic monomers, and reduce the ineffective hydrolysis of silane unsaturated hydrophobic monomers; second, its reaction product with water is weakly acidic, which can further inhibit the hydrolysis of silane unsaturated hydrophobic monomers, prevent intramolecular condensation of silane unsaturated hydrophobic monomers, and ensure the molecular structure integrity and synthesis quality of the thickener.

[0051] Further preferably, the pH adjuster is selected from one or more of sodium carbonate, sodium bicarbonate, ammonium bicarbonate, ammonia, sodium hydroxide, potassium hydroxide, triethanolamine, and citric acid, used to adjust the pH of the aqueous phase to a weakly acidic range of 5.5 to 6.5. This pH range is the optimized optimal reaction pH value, which can effectively inhibit the hydrolysis of a small amount of silane unsaturated hydrophobic monomers released into the aqueous phase, and ensure that the redox initiation system can smoothly initiate the polymerization reaction at a reaction temperature of 40℃ to 45℃, avoiding problems such as initiator failure and incomplete polymerization caused by excessively high or low pH.

[0052] This invention employs a reverse emulsion polymerization method to prepare a hydrophobically associating polyacrylamide thickener containing hyperbranched side chains. The specific steps are as follows: The first step is to prepare the oil phase: According to the above raw material ratio, add anhydrous white oil, surfactant, unsaturated fluorocarbon hydrophobic monomer, silane unsaturated hydrophobic monomer, and triethyl orthoformate to a dry reaction vessel. Start stirring at room temperature, control the stirring speed at 300 r / min to 500 r / min, and stir for 20 min to 30 min until all components are completely dissolved to form a homogeneous, anhydrous, and transparent oil phase system. This ensures that each oil phase is uniformly dispersed, providing a stable oil phase environment for subsequent pre-emulsification and polymerization reactions.

[0053] The second step is to prepare the aqueous phase: Under stirring conditions of 400 r / min to 600 r / min, add the framework monomer, functional hyperbranched monomer, chain transfer agent and ammonium persulfate to deionized water according to the above raw material ratio. Stir for 30 min to 40 min until all components are completely dissolved to form a homogeneous and transparent aqueous solution. Then add a pH adjuster to adjust the pH value of the solution to 5.5 to 6.5 to form a homogeneous and stable aqueous phase system. The third step is pre-emulsification: Under stirring conditions of 800 r / min to 1200 r / min, the prepared aqueous phase is slowly added dropwise to the oil phase at a rate of 5 mL / min to 10 mL / min. The dropping rate should not be too fast to avoid demulsification of the water-in-oil emulsion. After the addition is complete, high-speed shearing or ultrasonic emulsification is continued for 15 min to 20 min to form a stable, bluish-green water-in-oil pre-emulsion. At this point, the silane unsaturated hydrophobic monomers and unsaturated fluorocarbon hydrophobic monomers are effectively isolated in the external oil phase, preventing them from directly contacting the aqueous phase and causing hydrolysis or premature reaction. This provides a stable reaction environment for the subsequent interfacial polymerization reaction and ensures the effective grafting of functional hyperbranched monomers.

[0054] Step 4, Initiation of polymerization: Nitrogen gas is continuously introduced into the pre-emulsion for 20-30 minutes to completely remove oxygen from the system, preventing oxygen from inhibiting the initiation effect of the initiator and preventing oxidative degradation of molecular chains during polymerization. Then, the reaction system is heated to the target reaction temperature (40℃-45℃) and kept at a constant temperature for 0.5-1.5 hours to allow the monomers in the pre-emulsion to mix and activate fully, thereby improving the monomer polymerization efficiency. Subsequently, oil-soluble initiator and sodium bisulfite aqueous solution are slowly added dropwise through two independent drop windows at a rate of 2-5 mL / min, respectively, to maintain the system temperature stable at 40℃-45℃.

[0055] During the polymerization reaction, the system temperature is monitored in real time. If the rate of temperature rise in the reaction system exceeds 3℃ / min, the cold bath is immediately started to cool down the system to avoid problems such as monomer bursting and molecular chain degradation caused by excessive temperature. The reaction continues for 4h~6h until the system temperature stabilizes and there is no change. The polymerization reaction is then considered to be completely over, and the target copolymer emulsion can be obtained at this time.

[0056] Step 5, Post-processing: After the polymerization reaction is completed, the reaction product is transferred to a vacuum drying oven and dried at 95°C for 5 to 7 hours to allow the solvents (anhydrous acetone, anhydrous white oil, etc.) in the product to completely evaporate. Then, the dried product is placed in a pulverizer and pulverized, and passed through an 80-100 mesh sieve to remove unpulverized agglomerates, resulting in a powder with uniform particle size. After cooling to room temperature, the powder is discharged to obtain a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains.

[0057] The present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be noted that the scope of protection of the present invention is not limited to the following embodiments. All equivalent transformations made based on the technical solutions of the present invention shall fall within the scope of protection of the present invention.

[0058] Example 1 This embodiment provides a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains, which is prepared by reverse emulsion polymerization, specifically as follows: the mass ratio of the aqueous phase to the oil phase is m1:m2=1:1.

[0059] Based on the total mass m1 of the aqueous phase, the aqueous phase includes 15% framework monomers, 10% functional hyperbranched monomers, 0.08% chain transfer agent (sodium formate), 0.15% water-soluble initiator (ammonium persulfate and sodium bisulfite in a mass ratio of 2:1), and the remainder is deionized water.

[0060] Based on the total mass m2 of the oil phase, the oil phase includes 1.0% unsaturated fluorocarbon hydrophobic monomer (C9 dodecafluoroheptyl methacrylate), 0.9% silane unsaturated hydrophobic monomer (vinyltrimethoxysilane), 0.05% triethyl orthoformate, 10% surfactant (Span 80 and Tween 80 in a mass ratio of 6:1), 0.1% oil-soluble initiator (azobisisoheptanenitrile), and the balance is 15# anhydrous white oil.

[0061] The mass ratio of acrylic acid to acrylamide in the skeleton monomer is 1:4, and the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to the carboxyl-terminated hyperbranched macromonomer in the functional hyperbranched monomer is 14.7:0.3.

[0062] The specific method for preparing terminal carboxyl hyperbranched macromonomers is as follows: Step 1: Select hydroxyl-terminated hyperbranched polyester Boltorn H20 as the starting material, place it in a vacuum drying oven, and vacuum dry it for 4 hours at 80℃ and -0.1MPa to remove trace amounts of moisture from the raw material and avoid side reactions.

[0063] Step 2: In a three-necked flask equipped with a mechanical stirrer, a reflux condenser, and a nitrogen inlet, add 100 parts by mass of dried terminal hydroxyl hyperbranched polyester Boltorn H20, and then add 300 parts by mass of anhydrous acetone as a reaction solvent. Stir until the raw materials are completely dissolved, then add 1.0 part by mass of p-toluenesulfonic acid as a catalyst. Under continuous nitrogen protection, add maleic anhydride slowly dropwise at a molar ratio of hydroxyl groups of terminal hydroxyl hyperbranched polyester Boltorn H20 to maleic anhydride of 1:1.1. After the addition is complete, raise the temperature to 65°C and react at a constant temperature for 6 hours. Monitor the reaction progress by infrared spectroscopy. When the characteristic peak of the anhydride completely disappears, the reaction is considered to have reached the endpoint, and the reaction solution is obtained.

[0064] Step 3: Cool the reaction solution naturally to room temperature, slowly pour in excess ice-cold ether to precipitate, filter and collect the precipitate, wash three times with a mixed solvent of acetone and ether (volume ratio 1:3) to remove unreacted raw materials and byproducts, and then place the precipitate in a vacuum drying oven and vacuum dry at 40°C to constant weight to obtain a carboxyl-terminated hyperbranched macromonomer. The acid value was found to be 96% of the hydroxyl value of the hydroxyl-terminated hyperbranched polyester.

[0065] The preparation method of the hydrophobically associating polyacrylamide thickener containing hyperbranched side chains in this embodiment is as follows: The first step is to prepare the oil phase: Add the above-mentioned proportions of 15# anhydrous white oil, Span 80, Tween 80, C9 dodecafluoroheptyl methacrylate, vinyltrimethoxysilane, and triethyl orthoformate to a dry reaction vessel and stir at a rate of 500 r / min for 30 min to form a homogeneous, anhydrous, and transparent oil phase system.

[0066] The second step is to prepare the aqueous phase: dissolve the above-mentioned acrylic acid, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, carboxyl-terminated hyperbranched macromonomer, sodium formate, and ammonium persulfate in deionized water, stir at 600 r / min for 40 min, and then add citric acid as a pH adjuster to adjust the pH of the solution to 6.5 to form a stable aqueous phase system.

[0067] The third step is pre-emulsification: Under high-speed stirring at 1200 r / min, the prepared aqueous phase is slowly added dropwise to the oil phase at a rate of 10 mL / min. After the addition is completed, high-speed shearing continues for 20 min to form a stable, bluish-green water-in-oil pre-emulsion.

[0068] Step 4, initiating polymerization: Nitrogen gas is introduced into the pre-emulsion to remove oxygen for 30 min, then the system is heated to 45℃ and reacted at a constant temperature for 1.5 h. After that, oil-soluble initiator and sodium bisulfite aqueous solution are added dropwise through two independent drop windows at a rate of 5 mL / min, respectively, maintaining the system temperature at 45℃. The temperature is monitored during the reaction. If the temperature rise rate exceeds 3℃ / min, a cold bath is started to cool down. The reaction is continued for 6 h until the system temperature stabilizes and no longer changes. The reaction is then completed, and the target copolymer emulsion is obtained.

[0069] Step 5, post-processing: Place the target copolymer emulsion in a vacuum drying oven and dry it at 95°C for 7 hours. After pulverizing, pass it through a 100-mesh sieve, cool it to room temperature, and then discharge it to obtain a uniform and stable thickener product.

[0070] The performance of the thickener product prepared in this embodiment was tested, and the results are as follows: the degree of branching is 0.75; under high salt conditions with a total hardness of 50000 mg / L, the viscosity retention rate at room temperature is 83%, and the viscosity retention rate under high temperature conditions below 130℃ is 68%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is 88%; the shear recovery time is 24 s; the static suspended sedimentation rate of a 0.25% aqueous solution of this thickener, under the conditions of 20 / 40 mesh ceramsite proppant and a sand ratio of 35%, is 0.4 cm / min; the critical association concentration is 0.1%.

[0071] Example 2 This embodiment provides a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains, which is prepared by reverse emulsion polymerization, specifically as follows: the mass ratio of aqueous phase to oil phase m1:m2 = 1:0.6; Based on the total mass m1 of the aqueous phase, the aqueous phase includes 15% framework monomers, 3% functional hyperbranched monomers, 0.03% chain transfer agent (sodium formate), 0.1% water-soluble initiator, and the balance is deionized water; Based on the total mass m2 of the oil phase, the oil phase includes 0.1% unsaturated fluorocarbon hydrophobic monomer (C8 undecylfluorohexyl methacrylate), 0.1% silane unsaturated hydrophobic monomer (vinyltriethoxysilane), 0.01% triethyl orthoformate, 8% surfactant (Span 80 and Tween 80 in a mass ratio of 4:1), 0.05% oil-soluble initiator (azobisisobutyronitrile), and the balance is No. 5 anhydrous white oil; In the skeleton monomer, the mass ratio of acrylic acid to acrylamide is 1:4, and in the functional hyperbranched monomer, the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to the carboxyl-terminated hyperbranched macromonomer is 14:0.5.

[0072] In this embodiment, the terminal carboxyl hyperbranched macromonomer was prepared using a differentiated process. Specific preparation parameters are as follows: 100 parts by mass of dried terminal hydroxyl hyperbranched polyester Boltorn H20 were selected, and 280 parts by mass of anhydrous acetone were added as the reaction solvent. 0.8 parts by mass of p-toluenesulfonic acid were added as the catalyst. Maleic anhydride was added at a molar ratio of 1:1.05 (hydroxyl group of Boltorn H20 to maleic anhydride). The reaction was carried out at a constant temperature of 62°C for 5.0 h. The remaining post-treatment steps were consistent with those in Example 1. The acid value of the terminal carboxyl hyperbranched macromonomer prepared in this embodiment was found to be 93% of the hydroxyl value of the terminal hydroxyl hyperbranched polyester.

[0073] The preparation method of the hydrophobically associating polyacrylamide thickener containing hyperbranched side chains in this embodiment is as follows: The first step is to prepare the oil phase: Add the above-mentioned proportions of 5# anhydrous white oil, Span 80, Tween 80, C8 undecylfluorohexyl methacrylate, vinyltriethoxysilane, and triethyl orthoformate to a dry reaction vessel and stir at a rate of 300 r / min for 20 min to form a homogeneous, anhydrous, and transparent oil phase system.

[0074] The second step is to prepare the aqueous phase: dissolve the above-mentioned acrylic acid, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, carboxyl-terminated hyperbranched macromonomer, sodium formate, and ammonium persulfate in deionized water, stir at a rate of 400 r / min for 30 min, and then add ammonia water as a pH adjuster to adjust the pH value of the solution to 5.5 to form a stable aqueous phase system.

[0075] The third step is pre-emulsification: Under high-speed stirring at 800 r / min, the aqueous phase is slowly added dropwise to the oil phase at a rate of 5 mL / min. After the addition is complete, ultrasonic emulsification is continued for 15 min to form a stable, bluish-green water-in-oil pre-emulsion.

[0076] Step 4, initiating polymerization: Nitrogen gas is introduced into the pre-emulsion to remove oxygen for 20 min, then the system is heated to 40℃ and reacted at a constant temperature for 0.5 h; then, oil-soluble initiator and sodium bisulfite aqueous solution are added dropwise through two independent drop windows at a rate of 2 mL / min, respectively, maintaining the system temperature at 40℃. The temperature is monitored during the reaction. If the temperature rise rate exceeds 3℃ / min, a cold bath is started to cool down, and the reaction is continued for 4 h until the system temperature stabilizes and no longer changes. The reaction is then complete, and the target copolymer emulsion is obtained.

[0077] Step 5, post-processing: Place the target copolymer emulsion in a vacuum drying oven and dry it at 95°C for 5 hours. After pulverizing, pass it through an 80-mesh sieve, cool it to room temperature, and then discharge it to obtain a uniform and stable thickener product.

[0078] The performance of the thickener product prepared in this embodiment was tested, and the results are as follows: branching degree is 0.7; under high salt conditions with a total hardness of 50000 mg / L, the viscosity retention rate at room temperature is 80%, and the viscosity retention rate under high temperature conditions below 130℃ is 65%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is 85%; the shear recovery time is 30 s; the static suspended sedimentation rate of a 0.25% aqueous solution of this thickener, under the conditions of 20 / 40 mesh ceramsite proppant and a sand ratio of 35%, is 0.5 cm / min; the critical association concentration is 0.1%.

[0079] Example 3 This embodiment provides a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains, which is prepared by reverse emulsion polymerization, specifically as follows: the mass ratio of aqueous phase to oil phase m1:m2 = 1:0.8; Based on the total mass m1 of the aqueous phase, the aqueous phase includes 17.5% framework monomers, 6.5% functional hyperbranched monomers, 0.045% chain transfer agent (sodium formate), 0.225% water-soluble initiator, and the balance is deionized water; Based on the total mass m2 of the oil phase, the oil phase includes 0.55% unsaturated fluorocarbon hydrophobic monomer (C12 tridecafluorooctyl methacrylate), 0.5% silane unsaturated hydrophobic monomer (γ-methacryloyloxypropyltrimethoxysilane), 0.045% triethyl orthoformate, 12% surfactant (Span 80 and Tween 80 in a mass ratio of 5:1), 0.1% oil-soluble initiator (azobisisoheptanenitrile), and the balance is 10# anhydrous white oil; The mass ratio of acrylic acid to acrylamide in the skeleton monomer is 1:4.5, and the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to the carboxyl-terminated hyperbranched macromonomer in the functional hyperbranched monomer is 14.8:0.5.

[0080] In this embodiment, the terminal carboxyl hyperbranched macromonomer was prepared using a differentiated process. The specific preparation parameters are as follows: 100 parts by mass of dried terminal hydroxyl hyperbranched polyester Boltorn H20 were selected, and 290 parts by mass of anhydrous acetone were added as the reaction solvent. 0.5 parts by mass of p-toluenesulfonic acid was added as a catalyst. Maleic anhydride was prepared at a molar ratio of 1:1.08 (hydroxyl group of Boltorn H20 to maleic anhydride). The reaction was carried out at a constant temperature of 63°C for 5.5 hours. The remaining post-treatment steps were consistent with those in Example 1. The acid value of the terminal carboxyl hyperbranched macromonomer prepared in this embodiment was found to be 94% of the hydroxyl value of the terminal hydroxyl hyperbranched polyester.

[0081] The preparation method of the hydrophobically associating polyacrylamide thickener containing hyperbranched side chains in this embodiment is as follows: The first step is to prepare the oil phase: Add the above-mentioned proportions of 10# anhydrous white oil, Span 80, Tween 80, C12 tridecyl methacrylate, γ-methacryloyloxypropyltrimethoxysilane, and triethyl orthoformate to a dry reaction vessel and stir at a rate of 400 r / min for 25 min to form a homogeneous, anhydrous, and transparent oil phase system.

[0082] The second step is to prepare the aqueous phase: dissolve the above-mentioned acrylic acid, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, carboxyl-terminated hyperbranched macromonomer, sodium formate, and ammonium persulfate in deionized water, and stir at a rate of 500 r / min for 35 min until all components are completely dissolved. Then add citric acid as a pH adjuster to adjust the pH of the solution to 6.0 to form a stable aqueous phase system.

[0083] The third step is pre-emulsification: Under high-speed stirring at 1000 r / min, the prepared aqueous phase is slowly added dropwise to the oil phase at a rate of 7.5 mL / min. After the addition is completed, high-speed shearing is continued for 17.5 min to form a stable, bluish-green water-in-oil pre-emulsion.

[0084] Step 4, initiating polymerization: Nitrogen gas was introduced into the pre-emulsion to remove oxygen for 25 min, and then the system was heated to 42.5℃ and reacted at a constant temperature for 1 h. After that, oil-soluble initiator and sodium bisulfite aqueous solution were added dropwise through two independent drop windows at a rate of 3.5 mL / min, respectively, maintaining the system temperature at 42.5℃. The temperature was monitored during the reaction. If the temperature rise rate exceeded 3℃ / min, a cold bath was started to cool down the system. The reaction was continued for 5 h until the system temperature stabilized and no longer changed. The reaction was then completed, and the target copolymer emulsion was obtained.

[0085] Step 5, post-processing: Place the target copolymer emulsion in a vacuum drying oven and dry it at 95°C for 6 hours. After pulverizing, pass it through a 90-mesh sieve, cool it to room temperature, and then discharge it to obtain a uniform and stable thickener product.

[0086] The performance of the thickener product prepared in this embodiment was tested, and the results are as follows: the degree of branching is 0.75; under high salt conditions with a total hardness of 50000 mg / L, the viscosity retention rate at room temperature is 84%, and the viscosity retention rate under high temperature conditions below 130℃ is 69%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is 89%; the shear recovery time is 23 s; the static suspended sedimentation rate of a 0.25% aqueous solution of this thickener, under the conditions of 20 / 40 mesh ceramsite proppant and a sand ratio of 35%, is 0.35 cm / min; the critical association concentration is 0.1%.

[0087] Example 4 This embodiment provides a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains, which is prepared by reverse emulsion polymerization, specifically as follows: the mass ratio of aqueous phase to oil phase m1:m2=1:0.7; Based on the total mass m1 of the aqueous phase, the aqueous phase includes 20% framework monomers, 8% functional hyperbranched monomers, 0.15% chain transfer agent (sodium formate), 0.3% water-soluble initiator, and the balance is deionized water; Based on the total mass m2 of the oil phase, the oil phase includes 0.8% unsaturated fluorocarbon hydrophobic monomer (C9 dodecafluoroheptyl methacrylate), 0.7% silane unsaturated hydrophobic monomer (γ-methacryloyloxypropyltrimethoxysilane), 0.08% triethyl orthoformate, 16% surfactant (Span 80 and Tween 80 in a mass ratio of 5:1), 0.15% oil-soluble initiator (azobisisoheptanenitrile), and the balance is 10# anhydrous white oil; In the skeleton monomer, the mass ratio of acrylic acid to acrylamide is 1:5, and in the functional hyperbranched monomer, the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to the carboxyl-terminated hyperbranched macromonomer is 15:0.5.

[0088] In this embodiment, the terminal carboxyl hyperbranched macromonomer was prepared using a differentiated process. Specific preparation parameters are as follows: 100 parts by mass of dried terminal hydroxyl hyperbranched polyester Boltorn H20 were selected, and 310 parts by mass of anhydrous acetone were added as the reaction solvent. 0.5 parts by mass of triethylamine was added as the catalyst. Maleic anhydride was prepared at a molar ratio of 1:1.08 (hydroxyl group of Boltorn H20 to maleic anhydride). The reaction was carried out at a constant temperature of 63°C for 5.5 hours. The remaining post-treatment steps were consistent with those in Example 1. Testing showed that the acid value of the terminal carboxyl hyperbranched macromonomer prepared in this embodiment was 95% of the hydroxyl value of the terminal hydroxyl hyperbranched polyester.

[0089] The preparation method of the hydrophobically associating polyacrylamide thickener containing hyperbranched side chains in this embodiment is as follows: The first step is to prepare the oil phase: Add the above-mentioned proportions of 10# anhydrous white oil, Span 80, Tween 80, C9 dodecafluoroheptyl methacrylate, γ-methacryloyloxypropyltrimethoxysilane, and triethyl orthoformate to a dry reaction vessel and stir at a rate of 450 r / min for 28 min to form a homogeneous, anhydrous, and transparent oil phase system.

[0090] The second step is to prepare the aqueous phase: dissolve the above-mentioned acrylic acid, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, carboxyl-terminated hyperbranched macromonomer, sodium formate and ammonium persulfate in deionized water, stir at 550 r / min for 38 min, and then add citric acid as a pH adjuster to adjust the pH of the solution to 6.2 to form a stable aqueous phase system.

[0091] The third step is pre-emulsification: Under high-speed stirring at 1100 r / min, the prepared aqueous phase is slowly added dropwise to the oil phase at a rate of 8 mL / min. After the addition is completed, high-speed shearing is continued for 18 min to form a stable, bluish-green water-in-oil pre-emulsion.

[0092] Step 4, initiating polymerization: Nitrogen gas was introduced into the pre-emulsion to remove oxygen for 28 min, and then the system was heated to 43°C and reacted at a constant temperature for 1.2 h. After that, oil-soluble initiator and sodium bisulfite aqueous solution were added dropwise through two independent drop windows at a rate of 4 mL / min, respectively, maintaining the system temperature at 43°C. The temperature was monitored during the reaction. If the temperature rise rate exceeded 3°C / min, a cold bath was started to cool down the system. The reaction was continued for 5.5 h until the system temperature stabilized and remained unchanged. The reaction was then completed, and the target copolymer emulsion was obtained.

[0093] Step 5, post-processing: Place the target copolymer emulsion in a vacuum drying oven and dry it at 95°C for 6.5 hours. After pulverizing, pass it through a 90-mesh sieve, cool it to room temperature, and then discharge it to obtain a uniform and stable thickener product.

[0094] The performance of the thickener product prepared in this embodiment was tested, and the results are as follows: branching degree is 0.73; under high salt conditions with a total hardness of 50000 mg / L, the viscosity retention rate at room temperature is 82%, and the viscosity retention rate under high temperature conditions below 130℃ is 67%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is 87%; the shear recovery time is 26 s; the static suspended sedimentation rate of a 0.25% aqueous solution of this thickener, under the conditions of 20 / 40 mesh ceramsite proppant and a sand ratio of 35%, is 0.42 cm / min; the critical association concentration is 0.1%.

[0095] Example 5 This embodiment provides a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains, which is prepared by reverse emulsion polymerization, specifically as follows: the mass ratio of aqueous phase to oil phase m1:m2 = 1:0.9; Based on the total mass m1 of the aqueous phase, the aqueous phase includes 18% framework monomers, 5% functional hyperbranched monomers, 0.1% chain transfer agent (sodium formate), 0.2% water-soluble initiator, and the balance is deionized water; Based on the total mass m2 of the oil phase, the oil phase includes 0.3% unsaturated fluorocarbon hydrophobic monomer (C12 pentadecyl methacrylate), 0.3% silane unsaturated hydrophobic monomer (vinyltrimethoxysilane), 0.03% triethyl orthoformate, 9% surfactant (Span 80 and Tween 80 in a mass ratio of 4.5:1), 0.08% oil-soluble initiator (azobisisobutyronitrile), and the balance is 15# anhydrous white oil; The mass ratio of acrylic acid to acrylamide in the skeleton monomer is 1:4.8, and the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to the carboxyl-terminated hyperbranched macromonomer in the functional hyperbranched monomer is 14.5:0.4.

[0096] In this embodiment, the terminal carboxyl hyperbranched macromonomer was prepared using a differentiated process. Specific preparation parameters are as follows: 100 parts by mass of dried terminal hydroxyl hyperbranched polyester Boltorn H20 were selected, and 270 parts by mass of anhydrous acetone were added as the reaction solvent. 0.2 parts by mass of triethylamine were added as the catalyst. Maleic anhydride was prepared at a molar ratio of 1:1.03 (hydroxyl group of Boltorn H20 to maleic anhydride). The reaction was carried out at a constant temperature of 61°C for 4.5 hours. The remaining post-treatment steps were consistent with those in Example 1. The acid value of the terminal carboxyl hyperbranched macromonomer prepared in this embodiment was found to be 92% of the hydroxyl value of the terminal hydroxyl hyperbranched polyester.

[0097] The preparation method of the hydrophobically associating polyacrylamide thickener containing hyperbranched side chains in this embodiment is as follows: The first step is to prepare the oil phase: Add the above-mentioned proportions of 15# anhydrous white oil, Span 80, Tween 80, C12 pentadecyl methacrylate, vinyltrimethoxysilane, and triethyl orthoformate to a dry reaction vessel and stir at a rate of 350 r / min for 22 min to form a homogeneous, anhydrous, and transparent oil phase system.

[0098] The second step is to prepare the aqueous phase: dissolve the above-mentioned acrylic acid, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, carboxyl-terminated hyperbranched macromonomer, sodium formate, and ammonium persulfate in deionized water, and stir at a rate of 450 r / min for 32 min until all components are completely dissolved. Then, add ammonia water as a pH adjuster to adjust the pH of the solution to 5.8 to form a stable aqueous phase system.

[0099] The third step is pre-emulsification: Under high-speed stirring at 900 r / min, the prepared aqueous phase is slowly added dropwise to the oil phase at a rate of 6 mL / min. After the addition is completed, high-speed shearing continues for 16 min to form a stable, bluish-green water-in-oil pre-emulsion.

[0100] Step 4, initiating polymerization: Nitrogen gas was introduced into the pre-emulsion to remove oxygen for 22 min, and then the system was heated to 41℃ and reacted at a constant temperature for 0.8 h. After that, oil-soluble initiator and sodium bisulfite aqueous solution were added dropwise through two independent drop windows at a rate of 3 mL / min, respectively, maintaining the system temperature at 41℃. The temperature was monitored during the reaction. If the temperature rise rate exceeded 3℃ / min, a cold bath was started to cool down the system. The reaction was continued for 4.5 h until the system temperature stabilized and no longer changed. The reaction was then completed, and the target copolymer emulsion was obtained.

[0101] Step 5, post-processing: Place the target copolymer emulsion in a vacuum drying oven and dry it at 95°C for 5.5 hours. After pulverizing, pass it through an 85-mesh sieve, cool it to room temperature, and then discharge it to obtain a uniform and stable thickener product.

[0102] The performance of the thickener product prepared in this embodiment was tested, and the results are as follows: branching degree is 0.71; under high salt conditions with a total hardness of 50000 mg / L, the viscosity retention rate at room temperature is 81%, and the viscosity retention rate under high temperature conditions below 130℃ is 66%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is 86%; the shear recovery time is 28 s; the static suspended sedimentation rate of a 0.25% aqueous solution of this thickener, under the conditions of 20 / 40 mesh ceramsite proppant and 35% sand ratio, is 0.48 cm / min; the critical association concentration is 0.1%.

[0103] Example 6 This embodiment provides a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains, which is prepared by reverse emulsion polymerization, specifically as follows: the mass ratio of aqueous phase to oil phase m1:m2 = 1:0.75; Based on the total mass m1 of the aqueous phase, the aqueous phase includes 16% framework monomers, 9% functional hyperbranched monomers, 0.12% chain transfer agent (sodium formate), 0.25% water-soluble initiator, and the balance is deionized water; Based on the total mass m2 of the oil phase, the oil phase includes 0.7% unsaturated fluorocarbon hydrophobic monomer (C9 dodecafluoroheptyl methacrylate), 0.6% silane unsaturated hydrophobic monomer (vinyltriethoxysilane), 0.06% triethyl orthoformate, 14% surfactant (Span 80 and Tween 80 in a mass ratio of 5.5:1), 0.12% oil-soluble initiator (azobisisoheptanenitrile), and the balance being an equal mass mixture of No. 5 anhydrous white oil and No. 10 anhydrous white oil). The mass ratio of acrylic acid to acrylamide in the skeleton monomer is 1:4.2, and the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to the carboxyl-terminated hyperbranched macromonomer in the functional hyperbranched monomer is 14.9:0.5.

[0104] In this embodiment, the terminal carboxyl hyperbranched macromonomer was prepared using a differentiated process. Specific preparation parameters are as follows: 100 parts by mass of dried terminal hydroxyl hyperbranched polyester Boltorn H20 were selected, and 320 parts by mass of anhydrous acetone were added as the reaction solvent. 0.9 parts by mass of p-toluenesulfonic acid were added as the catalyst. Maleic anhydride was prepared at a molar ratio of 1:1.10 (hydroxyl group of Boltorn H20 to maleic anhydride). The reaction was carried out at a constant temperature of 64°C for 5.8 hours. The remaining post-treatment steps were consistent with those in Example 1. The acid value of the terminal carboxyl hyperbranched macromonomer prepared in this embodiment was found to be 95.5% of the hydroxyl value of the terminal hydroxyl hyperbranched polyester.

[0105] The preparation method of the hydrophobically associating polyacrylamide thickener containing hyperbranched side chains in this embodiment is as follows: The first step is to prepare the oil phase: add the above-mentioned compound anhydrous white oil, Span 80, Tween 80, C9 dodecafluoroheptyl methacrylate, vinyltriethoxysilane, and triethyl orthoformate into a dry reaction vessel and stir at a rate of 420 r / min for 26 min to form a homogeneous, anhydrous, and transparent oil phase system.

[0106] The second step is to prepare the aqueous phase: dissolve the above-mentioned acrylic acid, acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, carboxyl-terminated hyperbranched macromonomer, sodium formate, and ammonium persulfate in deionized water, stir at 520 r / min for 36 min, and then add citric acid as a pH adjuster to adjust the pH of the solution to 6.3 to form a stable aqueous phase system.

[0107] The third step is pre-emulsification: Under high-speed stirring at 1050 r / min, the prepared aqueous phase is slowly added dropwise to the oil phase at a rate of 9 mL / min. After the addition is completed, high-speed shearing is continued for 19 min to form a stable, bluish-green water-in-oil pre-emulsion.

[0108] Step 4, initiating polymerization: Nitrogen gas was introduced into the pre-emulsion to remove oxygen for 26 min, and then the system was heated to 44℃ and reacted at a constant temperature for 1.3 h. After that, oil-soluble initiator and sodium bisulfite aqueous solution were added dropwise through two independent dropping windows at a rate of 4.5 mL / min, respectively, maintaining the system temperature at 44℃. The temperature was monitored during the reaction. If the temperature rise rate exceeded 3℃ / min, a cold bath was started to cool down. The reaction was continued for 5.2 h until the system temperature stabilized and no longer changed. The reaction was then completed, and the target copolymer emulsion was obtained.

[0109] Step 5, post-processing: Place the target copolymer emulsion in a vacuum drying oven and dry it at 95°C for 6.2 hours. After pulverizing, pass it through a 95-mesh sieve, cool it to room temperature, and then discharge it to obtain a uniform and stable thickener product.

[0110] The performance of the thickener product prepared in this embodiment was tested, and the results are as follows: branching degree is 0.74; under high salt conditions with a total hardness of 50000 mg / L, the viscosity retention rate at room temperature is 83.5%, and the viscosity retention rate under high temperature conditions below 130℃ is 68.5%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is 88.5%; the shear recovery time is 22 s; the static suspended sedimentation rate of a 0.25% aqueous solution of this thickener, under the conditions of 20 / 40 mesh ceramsite proppant and a sand ratio of 35%, is 0.38 cm / min; the critical association concentration is 0.1%.

[0111] Comparative Example 1 This comparative example provides a polyacrylamide thickener prepared by reverse emulsion polymerization. This comparative example does not add carboxyl-terminated hyperbranched macromonomers, unsaturated fluorocarbon hydrophobic monomers, or silane unsaturated hydrophobic monomers; otherwise, it is the same as in Example 1.

[0112] Wherein: the mass ratio of aqueous phase to oil phase m1:m2 = 1:1; Based on the total mass m1 of the aqueous phase, the aqueous phase includes 15% framework monomer, 0.08% chain transfer agent (sodium formate), 0.15% water-soluble initiator (ammonium persulfate and sodium bisulfite in a mass ratio of 2:1), and the remainder is deionized water.

[0113] Based on the total mass m2 of the oil phase, the oil phase includes 0.05% triethyl orthoformate, 10% surfactant (Span 80 and Tween 80 in a mass ratio of 6:1), 0.1% oil-soluble initiator (azobisisoheptanenitrile), and the balance is 15# anhydrous white oil.

[0114] In this comparative example, the mass ratio of acrylic acid to acrylamide in the skeleton monomer is 1:4, and no functional hyperbranched monomers are added.

[0115] The performance of the thickener prepared in this comparative example was tested, and the results are as follows: the degree of branching is 0.42; under high salt conditions with a total hardness of 50000 mg / L, the viscosity retention rate at room temperature is 58%, and the viscosity retention rate under high temperature conditions below 130℃ is 41%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is 62%; the shear recovery time is 65 s; the static suspended sedimentation rate of a 0.25% aqueous solution of this thickener, under the conditions of 20 / 40 mesh ceramsite proppant and a sand ratio of 35%, is 1.2 cm / min; the critical association concentration is 0.28%.

[0116] Comparative Example 2 This comparative example provides a hydrophobic associative polyacrylamide thickener, prepared by reverse emulsion polymerization. This comparative example does not add terminal carboxyl hyperbranched macromonomers, and the rest is the same as in Example 1.

[0117] Wherein: the mass ratio of aqueous phase to oil phase m1:m2 = 1:1; Based on the total mass m1 of the aqueous phase, the aqueous phase includes 15% framework monomers, 10% functional hyperbranched monomers, 0.08% chain transfer agent (sodium formate), 0.15% water-soluble initiator (ammonium persulfate and sodium bisulfite in a mass ratio of 2:1), and the remainder is deionized water. Based on the total mass m2 of the oil phase, the oil phase includes 1.0% unsaturated fluorocarbon hydrophobic monomer (C9 dodecafluoroheptyl methacrylate), 0.9% silane unsaturated hydrophobic monomer (vinyltrimethoxysilane), 0.05% triethyl orthoformate, 10% surfactant (Span 80 and Tween 80 in a mass ratio of 6:1), 0.1% oil-soluble initiator (azobisisoheptanenitrile), and the balance is 15# anhydrous white oil.

[0118] In this process, the mass ratio of acrylic acid to acrylamide in the skeleton monomer is 1:4, and the only functional hyperbranching monomer used is 2-acrylamido-2-methylpropanesulfonic acid, eliminating the addition of terminal carboxyl hyperbranching macromonomers.

[0119] The performance of the thickener prepared in this comparative example was tested, and the results are as follows: the degree of branching is 0.55; under high salt conditions with a total hardness of 50000 mg / L, the viscosity retention rate at room temperature is 71%, and the viscosity retention rate under high temperature conditions below 130℃ is 53%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is 73%; the shear recovery time is 42 s; the static suspended sedimentation rate of a 0.25% aqueous solution of this thickener, under the conditions of 20 / 40 mesh ceramsite proppant and a sand ratio of 35%, is 0.85 cm / min; the critical association concentration is 0.18%.

[0120] Comparative Example 3 This comparative example provides a polyacrylamide thickener containing carboxyl-terminated hyperbranched side chains, prepared by reverse emulsion polymerization. This comparative example does not add unsaturated fluorocarbon hydrophobic monomers or silane unsaturated hydrophobic monomers, and the rest is the same as in Example 1.

[0121] Wherein: the mass ratio of aqueous phase to oil phase m1:m2 = 1:1; Based on the total mass m1 of the aqueous phase, the aqueous phase includes 15% framework monomers, 10% functional hyperbranched monomers, 0.08% chain transfer agent (sodium formate), 0.15% water-soluble initiator (ammonium persulfate and sodium bisulfite in a mass ratio of 2:1), and the remainder is deionized water. Based on the total mass m2 of the oil phase, the oil phase includes 0.05% triethyl orthoformate, 10% surfactant (Span 80 and Tween 80 in a mass ratio of 6:1), and 0.1% oil-soluble initiator (azobisisoheptanenitrile).

[0122] The mass ratio of acrylic acid to acrylamide in the skeleton monomer is 1:4, and the mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to carboxyl-terminated hyperbranched macromonomer in the functional hyperbranched monomer is 14.7:0.3, with the balance being 15# anhydrous white oil. The performance of the thickener prepared in this comparative example was tested, and the results are as follows: the degree of branching is 0.74; under high salt conditions with a total hardness of 50000 mg / L, the viscosity retention rate at room temperature is 66%, and the viscosity retention rate under high temperature conditions below 130℃ is 48%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is 70%; the shear recovery time is 38 s; the static suspended sedimentation rate of a 0.25% aqueous solution of this thickener, under the conditions of 20 / 40 mesh ceramsite proppant and a sand ratio of 35%, is 0.92 cm / min; the critical association concentration is 0.22%.

[0123] Based on the performance test data from Examples 1-6 and Comparative Examples 1-3, it is evident that the hydrophobically associating polyacrylamide thickener containing hyperbranched side chains, synergistically modified with terminal carboxyl hyperbranched side chains, medium- to long-chain fluorocarbon hydrophobic monomers, and silane unsaturated hydrophobic monomers, exhibits significantly superior overall performance compared to the polyacrylamide thickeners prepared in Comparative Examples 1-3 and the single-structure modified polyacrylamide thickeners. The hydrophobically associating polyacrylamide thickeners containing hyperbranched side chains prepared in each example utilize the synergistic effect of the hyperbranched topological molecular structure and the association and crosslinking of the two hydrophobic groups, resulting in higher molecular branching degree, high-temperature tackiness, high-salt water environment salt resistance, and high-speed shear resistance. Furthermore, the proppant exhibits lower sedimentation rate, faster shear deformation recovery rate, and lower critical association concentration, demonstrating excellent overall application performance. Due to the lack of hyperbranched topology or hydrophobic associative functional units of fluorocarbons and silanes, the cross-linked network structure of polymer molecules in each comparative example is loose and weak. As a result, they generally have defects such as low viscosity retention rate under high salt and high temperature conditions, poor viscosity stability under high shear conditions, deterioration of static suspension performance, long shear recovery time, and high critical association concentration.

[0124] Application examples This application example selects the hydrophobic associative polyacrylamide thickener with hyperbranched side chains prepared in Example 1 of this invention and conducts a field fracturing application test in well Su19-XX-XXH1 in the Wushen Banner oil and gas production area of ​​the Sulige Gas Field. The actual compatibility, construction stability, and production enhancement effect of this hydrophobic associative polyacrylamide thickener with hyperbranched side chains are verified through real well site construction conditions. The block where this test well is located is a typical high-water-cut tight sandstone gas reservoir with complex reservoir geology, strong heterogeneity, and a stable reservoir temperature of 130℃. High-salinity formation water with a hardness of 4500 mg / L is used for the field fluid preparation. The harsh conditions of high temperature and high salinity place extremely high demands on the temperature resistance, salt resistance, sand carrying capacity, and viscosity stability of the fracturing fluid thickener, thus providing a real and effective verification of the field practical performance of the thickener of this invention.

[0125] Based on the actual well conditions of the test well and the block construction specifications, the field application parameters were adapted and optimized. Specific construction parameters are as follows: the on-site thickener injection concentration was set to 0.25%, consistent with the concentration tested in the laboratory, ensuring that indoor test data and field application data are comparable; the average sand ratio during fracturing was 22.85%, with a maximum instantaneous sand ratio reaching 38%, significantly higher than the sand ratio in conventional fracturing of tight gas reservoirs, effectively increasing the scale of the reservoir stimulation fracture network; the fracturing displacement was controlled at 3.5 m³ / h. 3 The pressure remained stable at 32MPa~35MPa throughout the construction process, and all parameters were within the safe construction threshold range for this well. The construction conditions were controllable, safe and stable.

[0126] like Figure 1 As shown, the fracturing fluid system prepared using the hydrophobically associating polyacrylamide thickener with hyperbranched side chains prepared in Example 1 of this invention is uniform, transparent, stable, and shows no stratification, flocculation, or sedimentation. This indicates that the hydrophobically associating polyacrylamide thickener with hyperbranched side chains prepared in Example 1 of this invention exhibits excellent dispersibility and solubility in the fluid preparation water of high-salinity formations, making it suitable for complex water quality conditions in the field. Static and dynamic sand carrying tests were conducted using 20 / 40 mesh ceramsite proppant. Figure 2 As shown in the figure, under the field conditions of 30% sand ratio, the proppant initially exhibited a uniform suspension state, and only slight settling occurred after standing for 30 minutes. During the dynamic construction of the entire well section, the real-time monitoring showed that the sand settling rate was ≤0.15cm / min, which was better than the 0.35cm / min settling rate in the indoor simulation test. This confirms that under complex field conditions, the hydrophobic association and hyperbranched synergistic structure of the hydrophobic associative polyacrylamide thickener with hyperbranched side chains prepared in Example 1 of this invention can further enhance the viscoelasticity of the fracturing fluid, resulting in superior actual sand carrying and stabilization performance.

[0127] The fracturing operation proceeded smoothly throughout, with stable pump pressure and no significant fluctuations. No abnormal issues such as proppant settling, sand blockage, pump jamming, or system failure due to gel breaking occurred. The operation was successfully completed, fully verifying the excellent field compatibility and operational stability of the hydrophobic associating polyacrylamide thickener with hyperbranched side chains prepared in Example 1 of this invention. Field testing results showed that the fracturing fluid prepared with the hydrophobic associating polyacrylamide thickener with hyperbranched side chains prepared in Example 1 of this invention underwent thorough gel breaking, with a viscosity below 5 mPa·s and extremely low residue content, eliminating the problem of solid residue clogging reservoir pores. The system exhibited excellent high-temperature aging resistance, maintaining stable viscoelasticity and fracture support capacity under long-term formation conditions. It meets the standards for tight gas reservoir fracturing operations from multiple dimensions, including construction safety, reservoir protection, and long-term stability. After the fracturing was completed, production capacity testing and reservoir damage detection were carried out on the test well. The results showed that the average daily stable production of natural gas after fracturing reached 8,650 cubic meters / day. Compared with the adjacent wells in the same block, at the same formation, and in the same well area that were fractured using conventional polyacrylamide thickener, the average daily production increased by 2,155 cubic meters / day, an increase of 33.6%. At the same time, the reservoir matrix damage rate was ≤5%, which is far lower than the reservoir damage level of 12%~15% of conventional polyacrylamide fracturing fluid. This achieved the dual construction effect of efficient reservoir stimulation, significant production increase, and low reservoir damage.

[0128] To further verify the long-term stability and sustained production-enhancing effect of the thickener of this invention, continuous monitoring was conducted on the test well for six months. Long-term monitoring data showed that the well's natural gas production remained stable in the range of 8200-8600 cubic meters per day, without significant production decline, fracture closure, or decreased conductivity. The conductivity of the artificial fractures created by fracturing remained excellent, confirming that the colloidal network structure of the fracturing fluid formed by the solidified thickener of this invention possesses excellent long-term temperature resistance, salt resistance, and aging resistance, making it suitable for long-term formation conditions of high temperature and high salinity in tight gas reservoirs.

[0129] The combined results of indoor experiments and field well site measurements confirm that this invention, by constructing hyperbranched molecular side chains and coupling a synergistic association and crosslinking system of medium- and long-chain fluorocarbon hydrophobic monomers and silane unsaturated hydrophobic monomers, effectively solves the technical shortcomings of traditional polyacrylamide thickeners, such as poor temperature and salt resistance, weak shear resistance, insufficient sand-carrying stability, high reservoir damage, and poor long-term effectiveness. The hydrophobic associative polyacrylamide thickener containing hyperbranched side chains of this invention has a reasonable formulation, controllable process, and strong field applicability. It is suitable for the fracturing and production enhancement operations in tight sandstone gas reservoirs under high temperature, high salinity, and complex conditions, offering significant advantages in production enhancement, efficiency improvement, and reservoir protection. It also exhibits good long-term operational stability and possesses extremely high field promotion value and promising prospects for industrial application.

Claims

1. A hydrophobically associating polyacrylamide thickener containing hyperbranched side chains, characterized in that, The thickener is prepared by reverse emulsion polymerization and comprises an aqueous phase and an oil phase with a mass ratio of 1:0.6 to 1:

1. The aqueous phase comprises: a framework monomer, a functional hyperbranched monomer, a chain transfer agent, a water-soluble initiator, and deionized water; the framework monomer comprises acrylamide and acrylic acid; the functional hyperbranched monomer comprises 2-acrylamido-2-methylpropanesulfonic acid and a carboxyl-terminated hyperbranched macromonomer; the water-soluble initiator comprises ammonium persulfate and sodium bisulfite; and the chain transfer agent comprises sodium formate. The oil phase includes: anhydrous white oil, surfactant, hydrophobic monomer, dehydrating agent, and oil-soluble initiator; the surfactant includes Span 80 and Tween 80, and the hydrophobic monomer includes unsaturated fluorocarbon hydrophobic monomer and silane unsaturated hydrophobic monomer.

2. The hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 1, characterized in that, Based on the total mass of the aqueous phase, it includes 15%~20% framework monomers, 3%~10% functional hyperbranched monomers, 0.03%~0.15% chain transfer agents, 0.1%~0.3% water-soluble initiators, and the balance is deionized water.

3. The hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 2, characterized in that, The mass ratio of acrylamide to acrylic acid in the skeleton monomer is 1:4 to 1:

5.

4. The hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 2, characterized in that, The mass ratio of 2-acrylamido-2-methylpropanesulfonic acid to the carboxyl-terminated hyperbranched macromonomer in the functional hyperbranched monomer is (14~15): (0.3~0.5).

5. The hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 4, characterized in that, The carboxyl-terminated hyperbranched macromonomer was prepared by esterification of a hydroxyl-terminated hyperbranched polyester with maleic anhydride. In the esterification reaction, the molar ratio of the hydroxyl group of the hydroxyl-terminated hyperbranched polyester to the maleic anhydride was 1:1.0 to 1:1.1, the reaction temperature was 60℃ to 65℃, and the reaction time was 4h to 6h. The acid value of the obtained carboxyl-terminated hyperbranched macromonomer was 92% to 96% of the hydroxyl value of the hydroxyl-terminated hyperbranched polyester.

6. The hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 5, characterized in that, The terminal hydroxyl hyperbranched polyester has at least one of the following structural features: (a) a branching degree of 0.4 to 0.7; (b) a backing structure of aliphatic hyperbranched polyester; (c) a backing structure of aromatic hyperbranched polyester; (d) a hydroxyl value of 490 mg KOH / g to 560 mg KOH / g; (e) a number-average molecular weight of 1000 to 10000; and (f) an average number of terminal hydroxyl groups of 8 to 48 per molecule.

7. The hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 1, characterized in that, Based on the total mass of the oil phase, it includes 0.1%~1.0% unsaturated fluorocarbon hydrophobic monomers, 0.1%~0.9% silane unsaturated hydrophobic monomers, 0.01%~0.08% dehydrating agent, 8%~16% surfactant, 0.05%~0.15% oil-soluble initiator, and the balance is anhydrous white oil.

8. The hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 7, characterized in that, The surfactant has a mass ratio of Span 80 to Tween 80 of 4:1 to 6:1, and the dehydrating agent is triethyl orthoformate.

9. The hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 7, characterized in that, The unsaturated fluorocarbon hydrophobic monomer is a medium- to long-chain fluorinated acrylate; the silane unsaturated hydrophobic monomer is one or more of γ-methacryloyloxypropyltrimethoxysilane, vinyltriethoxysilane, and vinyltrimethoxysilane.

10. The hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 1, characterized in that, The hydrophobic associative polyacrylamide thickener containing hyperbranched side chains uses polyacrylamide as its molecular backbone, on which terminal carboxyl hyperbranched side chains, fluorocarbon hydrophobic groups, and silane crosslinking active groups are grafted respectively; the degree of branching of the hydrophobic associative polyacrylamide thickener containing hyperbranched side chains is 0.70~0.75, and the molecular weight is 13 million.

11. The hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 1, characterized in that, The hydrophobic associative polyacrylamide thickener containing hyperbranched side chains has the following performance parameters: Under high-salt conditions with a total hardness of 50,000 mg / L, the viscosity retention rate at room temperature is ≥80%, and the viscosity retention rate under high-temperature conditions below 130℃ is ≥65%; under high-speed shear conditions of 3400 r / min, the viscosity retention rate is ≥85%; the shear recovery time is ≤30s; a 0.25% aqueous solution of hydrophobic associating polyacrylamide thickener containing hyperbranched side chains, with 20 / 40 mesh ceramsite support and a sand ratio of 35%, has a static suspended sedimentation rate of ≤0.5 cm / min; the critical association concentration is 0.1%.

12. A method for preparing a hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to any one of claims 1 to 11, characterized in that, The reverse emulsion polymerization method includes the following steps: Anhydrous white oil, surfactant, unsaturated fluorocarbon hydrophobic monomer, silane unsaturated hydrophobic monomer, and dehydrating agent are mixed and stirred evenly to obtain the oil phase; Acrylamide, acrylic acid, 2-acrylamido-2-methylpropanesulfonic acid, carboxyl-terminated hyperbranched macromonomer, sodium formate, and ammonium persulfate were dissolved in deionized water, the pH of the system was adjusted to 5.5-6.5, and the mixture was stirred evenly to obtain an aqueous phase. The aqueous phase is slowly added to the oil phase at a constant rate, and continuous high-speed shear emulsification is carried out to obtain a water-in-oil pre-emulsion; Nitrogen gas was introduced into the pre-emulsion to remove oxygen. After the oxygen was removed, the temperature was raised to the target reaction temperature. An oil-soluble initiator and an aqueous solution of sodium bisulfite were added dropwise, and the mixture was kept at a constant temperature for 4-6 hours to obtain a copolymer emulsion with a dual network topology. The copolymer emulsion was vacuum dried, pulverized, and sieved to obtain a hydrophobic associative polyacrylamide thickener containing hyperbranched side chains.

13. The method for preparing a hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 12, characterized in that, The stirring speed for oil phase preparation was 300 r / min to 500 r / min, and the stirring time was 20 min to 30 min. The stirring speed for aqueous phase preparation was 400 r / min to 600 r / min, and the stirring time was 30 min to 40 min. The droplet acceleration rate of aqueous phase was 5 mL / min to 10 mL / min, and the high-speed shear emulsification time was 15 min to 20 min.

14. The method for preparing a hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 12, characterized in that, The nitrogen deoxygenation time for the pre-emulsion is 20-30 minutes, the target reaction temperature is 40-45℃, and the initiator drop rate is 2-5 mL / min. When the temperature rise rate exceeds 3℃ / min during polymerization, a cold bath is used for cooling.

15. The method for preparing a hydrophobically associating polyacrylamide thickener containing hyperbranched side chains according to claim 13, characterized in that, The vacuum drying temperature is 95℃, the drying time is 5h~7h, and the powder is passed through an 80-100 mesh sieve.

16. The application of the hydrophobically associating polyacrylamide thickener containing hyperbranched side chains as described in claim 1 in fracturing fluids for oil and gas reservoirs, characterized in that, Using water as a solvent, a hydrophobic associative polyacrylamide thickener with hyperbranched side chains was added at a concentration of 0.25% to prepare fracturing fluid. The fracturing fluid prepared was suitable for fracturing operations in high-salinity oil and gas reservoirs with a temperature ≤220℃, and the maximum sand ratio reached 38%.